If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + -8x) = 35 + -8x (1 * 3 + -8x * 3) = 35 + -8x (3 + -24x) = 35 + -8x Solving 3 + -24x = 35 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 3 + -24x + 8x = 35 + -8x + 8x Combine like terms: -24x + 8x = -16x 3 + -16x = 35 + -8x + 8x Combine like terms: -8x + 8x = 0 3 + -16x = 35 + 0 3 + -16x = 35 Add '-3' to each side of the equation. 3 + -3 + -16x = 35 + -3 Combine like terms: 3 + -3 = 0 0 + -16x = 35 + -3 -16x = 35 + -3 Combine like terms: 35 + -3 = 32 -16x = 32 Divide each side by '-16'. x = -2 Simplifying x = -2
| 8-6.7(6-15-7)+7= | | 5x-(4x+3)+6=8 | | -896=905 | | 6x-4x+10=x+6 | | (10-3i)-(0-4i)= | | x-5/4-2=x-5/3 | | (x^2/y)/(x/y^2) | | 29f=145 | | 27=p/17 | | 2(3-x)=4-5x | | (2n+21)+(4n+15)= | | z/28=14 | | 90=11x+9+2x | | 7-2n=n-7 | | X^2-6x+45= | | 8d+2d+5d+6=5d | | x^2-5x-13=23 | | 0.55=z/-3 | | z/16=-24 | | -3(5t-5)+6t=2t-2 | | K+3=1d | | 8x+4x-3x=24 | | -5+3x=3(x-1)-2 | | 15=c/12 | | 2.1r+.02q=3.16-.2r | | -205=v-634 | | 6/4y-12=6 | | 4x-3(6-2x)=3x+4 | | 8y=384 | | 7x-4=7x-9 | | Y=3-3/2x | | c-150=980 |